MEMPELAJARI JALUR DISTRIBUSI DAN PENANGANAN PASCAPANEN STRAWBERRY DARI KECAMATAN BATURITI KE KOTA DENPASAR - Sapta Nugraha, I Gusti Made Dwi; Suryawan Wiranatha, A.A.P.Agung; Wrasiati, Ni Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aims of  this study were  1) to find out the distribution strawberry that produce in Baturiti to Denpasar, 2) to find out post-harvest handling in each distribution line 3) to determine the marketing and profit margins of each distribution from Baturiti to Denpasar. This study was using survey method with 20 responden of strawberry farmer. The results of this study showed that there were 3 distribution line of strawberry from Baturiti to Denpasar and all lines had experienced in sorting and grading on the collectors and traders. The highest marketing margin was Rp 24,000 / kg margin was Rp 11,300 /kg which were found in line 2 (Farmer-Collectors-Retailer-Consumer). Meanwhile the lowest marketing margin was Rp 17,000 /kg and the lowest profits margin was Rp 3,814 /kg which were found in line 3 (Collectors-Farmer-Consumer Wholesalers Catering).
Keywords: 79